Multiply (3-a) by (5-2a)?

2 Answers
Feb 19, 2018

15 - 11a + 2a^2

Explanation:

(3 - a)(5 - 2a) expanded = 15 - 6a - 5a + 2a^2
add like terms and you get 15 - 11a + 2a^2

Feb 19, 2018

2a^2-11a+15

Explanation:

(3-a)*(5-2a)
Multiply each term in the left bracket by each term in the right bracket.
a times a number looks like this a*3=3a
If you multiply it by itself its like this a*a=a^2
so

3*5 =15

3*(-2a)=-6a

(-a)*5=-5a

(-a)*(-2a)=2a^2

Arrange in order of a^2+a+#

2a^2-6a-5a+15
2a^2-11a+15